Evaluation of groundwater quality for domestic purposes and human health risk assessment for arsenic and manganese exposure in Cu Chi district, Ho Chi Minh city, Vietnam - Ha Lan Nguyen; Viet Ky Nguyen; Van Ngo Dau; Thi Phi Oanh Tran (Vietnam Journal of Science, Technology and Engineering, 2020)
Water is extremely important to all life currently, the Cu Chi district has been provided with one hundred percent clean water. However, due to long-standing habits and easy extraction, citizens are still using groundwater daily for water consumption and cooking. Therefore, in this study, the use of groundwater from the middle-upper Pleistocene aquifer in the Cu Chi district of Ho Chi Minh city, for domestic and drinking purposes was investigated. In terms of pH and Fe, NH 4 +, NO3-, As and Mn content, data were collected from central water supply stations under the operation of the Centre for Rural Water Supply and Sanitation (CERWASS). Furthermore, samples collected from 94 households and water supply stations were also evaluated for groundwater quality via pH and Fe, As, Hg, Cd, Pb, Cr6+ and CN- concentration. On the other hand, a human health risk assessment for carcinogenic substances (As) and non-carcinogenic substances (Mn) was performed by a variety of assessments including the susceptibility to contamination according to the DRASTIC index, which weights water risks by applying a semi-quantitative model. Because pollution is inevitable with today’s modernization and industrialization, these research results contribute to management and control measures deeply needed to achieve and maintain a safe water supply, thereby ensuring the health and safety for the communities in the Cu Chi district.